Factors influencing consumers' intention and attitude towards eating green - Tham, Shu Wen (2023)
The aim of this research is to study the consumers' attitude and intention toward eating green. A set of 300 questionnaires were distributed to respondents via Google Forms, and the data collected were subjected to analysis using IBM SPSS software. Descriptive analysis, reliability analysis, and inferential analysis were employed to interpret the gathered data. The study outcomes revealed two relationships between independent and dependent variables. The first IV-DV relationship suggested that the attitude towards eating green was influenced by health consciousness and food safety concern. Meanwhile, the second IV-DV relationship indicated that the intention towards eating green was influenced by the attitude towards eating green and subjective norm. However, it is important to note limitations in this research, which include the cross-sectional study, understanding “green food” term, and limited perspective of study. Hence, the recommendations of use of longitudinal study, conduct in-depth interview, and further examined other perspective in future study were discussed further in subsequent chapters for future research.